Sustainable management strategies for degraded subak rice fields in South Denpasar, Bali - Ambarini, Lina Anandari Dwi; Frimawaty, Evi; Herdiansyah, Herdis (Journal of Degraded and Mining Lands Management, 2026)
Rapid urbanization has accelerated the degradation of subak rice fields in Bali, manifested through pollution of irrigation channels and reduced agricultural productivity. This study assessed the extent and characteristics of land degradation in South Denpasar and formulated sustainable management strategies for restoring the ecological and cultural integrity of the subak system. The Logical Framework Approach (LFA) was applied to identify key problems, analyze causal relationships, and develop measurable strategies. Data were obtained through questionnaires, interviews, field observations, and document analysis. Results showed that approximately 87 hectares of subak land were lost within five years, driven by weak spatial enforcement, domestic and industrial waste pollution, and limited farmer regeneration. The study formulated five priority strategies: (1) enforcement of land use regulations, (2) economic incentives for conservation farming, (3) integration of Tri Hita Karana values, (4) farmer capacity building through digital technology and (5) improved irrigation maintenance. The research highlights that sustaining the subak system requires a multi dimensional management approach integrating ecological restoration, socio economic empowerment, and cultural revitalization. Adoption of this framework by local authorities can enhance urban land governance, strengthen farmer livelihoods, and preserve Bali’s cultural agricultural heritage amid ongoing urban pressures.